Kreacja przestrzeni oczami zwierząt. "Sprawiedliwość owiec. Filozoficzna powieść kryminalna" Leonie Swann = Space seen through the eyes of animals in "Three bags full. A sheep detective story" by Leonie Swann - Owcarz, Roksana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the paper is to discuss space seen through the eyes of animals in a contemporarycrime novel. The category of space considered in the study is a dichotomous plane where the good(the sacred) and the evil (the profane) clash. The author of the article has selected "Three Bags Full"by Leonie Swann for her analysis and so she has identified in the novel principal areas of the spaceand the roles they play, as well as the relationships between the characters and the space. The spacein the novel is limited and the characters perceive it in the categories of closeness and distance, offamiliarity/ownership and foreignness.
Keywords: Swann, Leonie (1975- ); literatura niemiecka - tematyka - 21 w.; powieść kryminalna